Carrot fiber (CF) composite films for antioxidant preservation: Particle size effect. (20th January 2016) - Idrovo Encalada, Alondra M.; Basanta, Maria F.; Fissore, Eliana N.; De'Nobili, Maria D.; Rojas, Ana M.
Highlights: Particle size (53, 105 and 210 μm) effect of isolated carrot fibers (CF) was studied. CF showed pectins, and co-extracted phenolics and carotenoids with antioxidant effect. CF and ascorbic acid were used for antioxidant low methoxyl pectin-based composites. Particle size affected hydration properties of CF and mechanical performance of films. Loaded ascorbic acid got the highest stability to hydrolysis in 53-μm-CF composite. Abstract: The effect of particle size (53, 105 and 210 μm) of carrot fiber (CF) on their hydration properties and antioxidant capacity as well as on the performance of the CF-composite films developed with commercial low methoxyl pectin (LMP) was studied. It was determined that CF contained carotenoids and phenolics co-extracted with polysaccharides (80%), rich in pectins (15%). CF showed antioxidant activity and produced homogeneous calcium–LMP-based composites. The 53-μm-CF showed the lowest hydration capability and produced the least elastic and deformable composite film due probably to CF bridged by calcium-crosslinked LMP chains. Antioxidant activity associated to the loaded CF was found in composites. Whenl -(+)-ascorbic acid (AA) was also loaded, its hydrolytic stability increased with the decrease in CF-particle size, showing the lowest stability in the 0%-CF- and 210 μm-CF-LMP films. Below ≈250 μm, the particle size determined the hydration properties of pectin-containing CF, affecting the microstructure and water mobility in composites.